Loop‐mediated isothermal amplification for the rapid detection of Gardnerella vaginalis. (21st September 2018) - Higashide, Satoshi; Cho, Otomi; Matsuda, Yuko; Ogishima, Daiki; Kurakado, Sanae; Sugita, Takashi
ABSTRACT: The aim of this study was to develop a method for the rapid detection of Gardnerella vaginalis, which is proposed to play a key role in the pathogenesis of bacterial vaginosis. Specific loop‐mediated isothermal amplification (LAMP) primers were designed and used to detect target DNA within 45 min under isothermal conditions. Comparative screening indicated that the LAMP assay is superior to PCR in terms of rapidity, and is equivalent in sensitivity and specificity. This LAMP assay can be used for rapid screening and detection of G. vaginalis in vaginal samples; the limit of detection is 10 fg DNA.